A Study on Emergence of Cryptocurrency in the Modern World - Dheeraj Sai Ram Raju; Sneha R (Jurnal Ekonomi dan Bisnis Digital, 2023)
21st century is a digital world, where new and improved tech is introduced on a daily basis, in short, it is an ever evolving world, Cryptocurrency latest inclusion of this trend, which was launched in 2009. In this paper you read about the emergence of Cryptocurrency, how it’s created and some of the major cons of it. Cryptocurrencies usually run on private blockchains- which are digitally distributed decentralized ledger that exist across a network and in this blockchains, every transaction is recorded and it also controls and oversees the transactions and maintains an updated data of existing users and their Crypto related digital portfolios, when ever a new unit of Crypto is created, blockchains store their unique code to avoid duplicates. Many experts believe Cryptocurrency will be a flagship currency of the digital world and because it doesn’t use any third parties in transaction its considered to be a game changer and if the predictions of Analyst do come true then many investors, brads, businesses, may also join the trend due to the growing popularity and benefits.